Curtailing Pollution due to Processes on Plastic Disposal - Shah, Nita H.; Jayswal, Ekta N.; Suthar, Ankush H. (Journal of Environmental Accounting and Management, 2026)
Though the government has ruled ``Say No to Plastic'', plastic usage is increasing day by day. It is observed since last three decades that each process of plastic creates pollution affecting degradation of environmental resources like air, soil and water. The proposed mathematical model contains these three pollutions with its issues having a dynamical system of nonlinear differential equations. Feasible region contains three equilibrium points pollution-free, water-pollution free and optimum issue point. Basic reproduction number and center manifold theory is used for analyzing the local stability of a model. Castillo-Chavez theory with detailed computation has been used to check global dynamical behavior of equilibrium points and also gives the existence of backward bifurcation of plastic usage. To optimize the pollution, optimal control has been applied to the system. Graphical analysis is carried out.